Palladium-catalyzed decarboxylative C3-acylation of benzofurans and benzothiophenes with α-oxocarboxylic acids via direct sp2 C–H bond activation. Issue 8 (25th February 2015) - Gong, Wei-Jie; Liu, De-Xian; Li, Fei-Long; Gao, Jun; Li, Hong-Xi; Lang, Jian-Ping
Abstract: An efficient approach to decarboxylative C3-acylation of benzothiophenes or benzofurans with α-oxocarboxylic acids via palladium-catalyzed C–H bond activation was developed. This method was compatible with a variety of functional groups and provided an attractive route to 3-acylbenzothiophenes and 3-acylbenzofurans in good to high yields. Graphical abstract: